2014
DOI: 10.1371/journal.pone.0102266
|View full text |Cite
|
Sign up to set email alerts
|

The mtDNA nt7778 G/T Polymorphism Augments Formation of Lymphocytic Foci but Does Not Aggravate Cerulein-Induced Acute Pancreatitis in Mice

Abstract: A polymorphism in the ATP synthase 8 (ATP8) gene of the murine mitochondrial genome, G-to-T transversion at position 7778, has been suggested to increase susceptibility to multiple autoimmune diseases, including autoimmune pancreatitis (AIP). The polymorphism also induces mitochondrial reactive oxygen species generation, secretory dysfunction and β-cell mass adaptation. Here, we have used two conplastic mouse strains, C57BL/6N-mtAKR/J (B6-mtAKR; nt7778 G; control) and C57BL/6N-mtFVB/N (B6-mtFVB; nt7778 T), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…At the same time a pancreatic β cell dysfunction, as well as an altered mitochondrial morphology in spleen cells, could be demonstrated (21). Pancreatic acini of 12-month-old mtFVB mice, by trend, had also enhanced ROS levels in comparison to mtAKR mice (20). However, in a corresponding in vivo study, no aggravation of acute pancreatitis in mtFVB strain was observed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…At the same time a pancreatic β cell dysfunction, as well as an altered mitochondrial morphology in spleen cells, could be demonstrated (21). Pancreatic acini of 12-month-old mtFVB mice, by trend, had also enhanced ROS levels in comparison to mtAKR mice (20). However, in a corresponding in vivo study, no aggravation of acute pancreatitis in mtFVB strain was observed.…”
Section: Discussionmentioning
confidence: 90%
“…It would, thus, impact the whole respiratory chain, influencing ROS and ATP production. Recently, the impact of the nt7778 G/T polymorphism on cell function has been studied in different tissues (19)(20)(21)(22), as well as its effects on anxiety and stress reactivity (23,24).…”
Section: Encodes For the Respiratory Chain Proteins Genetic Alteratimentioning
confidence: 99%
“…Most recently, we have identified in the same mouse strain CD4 + /CD44 high memory T-cells as an important link between genetic susceptibility and emergence of the disease [22]. Noteworthy, pancreatic autoimmune lesions have been shown in some mouse models to progress with increasing age [23], a phenomenon that might, at least in part, be related to a less efficient action of inhibitory immune cells in aged animals.…”
Section: Introductionmentioning
confidence: 99%